Never never eaudiobook - Patterson, James (Detective Harriet Blue, 2017)
The Instant #1 New York Times and USA Today Bestseller Harry Blue is the top Sex Crimes investigator in her department. But even she didn't see this coming: her own brother arrested for the grisly murders of three beautiful young women. "For her own good," she's been sent to a desolate location and assigned to a new "partner." But is he actually meant to be a watchdog? In her strange new home, Harry she vanishes in a place where no one would ever think to look for her.